Ensuring Equality in Education Access: The Dynamics and Challenges for Vietnamese Ethnic Minority Girls - Nguyen Thi Hong Yen; Nguyen Van Hoi (Advanced Studies on Socio-Economy Development, 2023)
Education access is one of the critical human rights that has been decided for the development of everyone and has been codified in the international and national legal systems. Despite important achievements in ensuring and promoting fundamental human rights in general, with the characteristics of being one of the most vulnerable in society, ethnic minority girls experienced discrimination and double inequality in benefiting their rights, including access to education. Regarding the education right of girls in the ethnic minority in Vietnam today, the following article focuses on the following matters: (i) Analysing the Vietnamese legal framework in ensuring the education right of ethnic minority girls; (ii) Presenting the difficulties and challenges in ensuring this right for ethnic minority girls in Vietnam; (iii) Proposing necessary recommendations for the Government to improve the enjoyment of the right for Vietnamese ethnic minority girls in the upcoming time. Keywords: Education Access, Equality, Ethnic Minority Girls, Vietnam, Women's rights